Human-Computer Interaction in Smart Living Environments: Challenges and Opportunities - Prof. Prabodhan U. Patil, Prof. Manisha C. Pagar, Dr. Tushar K. Savale; Prof. Savita B. Mogare, Dr. Nainesh Mutha, Dr. Hemant F. Wanjare (Journal of Informatics Education and Research, 2024)
The proliferation of smart technologies in living environments has ushered in an era where humans and computers interact more intimately than ever before. This research paper delves into the complex landscape of Human-Computer Interaction (HCI) within the context of smart living environments, shedding light on the multifaceted challenges and exciting opportunities that lie ahead. In this exploration, we first review the fundamental concepts and technologies that underpin smart living environments, emphasizing the centrality of HCI in bridging the gap between humans and the myriad of interconnected devices and systems that constitute these environments. We then identify and analyze key challenges such as user privacy, security, usability, and adaptability, which continue to shape the HCI landscape in smart living. The paper also highlights the emerging opportunities for HCI research, including the integration of augmented reality (AR), virtual reality (VR), and natural language processing (NLP) into smart living systems, fostering more intuitive and seamless interactions. Additionally, it discusses the potential for personalized and context-aware HCI solutions that enhance user experiences and promote inclusivity. By addressing these challenges and harnessing these opportunities, this research seeks to provide valuable insights for HCI researchers, designers, and policymakers, ultimately contributing to the development of smarter and more user-friendly living environments that enhance our quality of life while respecting our fundamental rights and values.